Evolution of a Fault-Controlled, Deep-Water Sub-Basin, Tabernas, SE Spain - Baudouy, Lucie; Haughton, Peter D. W.; Walsh, John J. (Frontiers in Earth Science, 2021)
The Neogene Tabernas Basin, SE Spain, provides important evidence at outcrop for the interplay between tectonic deformation of the sea floor, slope instability and turbidity current behaviour. Dextral-oblique strike-slip faults and associated folds propagated along the basin axis to deform the palaeo-sea floor, creating structurally-controlled depressions in which turbidity currents were trapped and ponded. EW-trending syn-depositional faults define a narrow sub-basin that subsided asymmetrically as a negative flower structure. The sub-basin contains an expanded succession (>300 m of ponded turbidite sheets, debrites and slumps) along its northern margin flanked by the principal fault strand defined by a wide zone of sheared and calcite-veined marl. A narrower fault zone with a smaller displacement marks the southern margin of the sub-basin and the fill close to it is thin with internal discordances, evidence of local failure and southward thinning of sandstone sheets. Both northern and southern faults ‘died’ at the same stratigraphic level and were overstepped by basin floor turbidites showing evidence of weaker and longer-range topographic confinement. As turbidites healed and aggraded out of the sub-basin to progressively onlap the southern margin of the basin, major gravity failures occurred emplacing thick (>100 m) mass-transport complexes. The first initially reworked the southern part of the sub-basin fill together with the early onlap wedge, the second remobilised the onlap wedge, and the third records failure of the upper part of the slope well above the wedge. The first two were toe-confined failures, the third and furthest travelled was confined by basin axis topography. All three failures are lateral to or directly overlain by ‘megabed’ sheets on the basin floor, implying either a common trigger (earthquakes) or slope instability following reflection of large volume flows. Tabernas turbidites highlight the role of basin tectonics (as opposed to up-dip supply and sea level fluctuations) in directly impacting on deep-water processes and stratigraphy. Small deep-water transtensional sub-basins opened up along long transfer faults accommodating regional extension.